A stable photonic generation scheme of triangular waveform with double frequency and variable power. Issue 12 (12th July 2019) - Zhang, Yinling; Shang, Tao; Gao, Yan; Li, Gufeng; Chen, Dan
ABSTRACT: A microwave photonic generation scheme of triangular waveform using cascaded dual-drive Mach-Zehnder modulators (DDMZMs) and FBG is proposed. We show that a frequency-doubled and power-variable triangular waveform can be obtained. The double frequency can reduce the high-frequency requirement of the local oscillation signal (LO) source. The introduction of the second modulator can improve the stability of the scheme. The simulation results show that the power of the triangular is variable; the stability is optimized when the first modulation index is in 0 1; the similarity coefficient is greater than 0.998, which is 0.006 higher than one-stage-modulation scheme. Meanwhile, the similarity coefficient remains over 0.992 when the DC drifting difference value of D D M Z M 1 and D D M Z M 2 is in −90 60 mV, and it remains over 0.99 when the phase difference of the two LO sources varies from −10° to 10°. It verifies the tolerance of DC drifting and phase desynchrony of the system.